XÁC ĐỊNH MỘT SỐ THAM SỐ HOẠT ĐỘNG DÔNG SÉT TỪ CHUỖI SỐ LIỆU MÔ PHỎNG - Sơn, Hoàng Hải; Anh, Nguyễn Xuân; Huy, Lê Việt; Thành, Phạm Xuân (Vietnam Journal of Earth Sciences, 2011)
Determination of lightning activity parameters from lightning simulation dataIn this paper, lightning activity parameters could be listed, including: moving speed of thundercloud, radius of thundercloud, storm duration, number of cell thundercloud, and distance between the cell of thundercloud for three difference types of thundercloud is determined using lightning simulation data. The first of all, thundercloud is divided into three different forms (similarity the way division of Peckham) which is based on their presumed parameters. Next, determination of lightning simulation data based on the parameters assumed above. Finally, using the method of correlation analysis space and time of Finke and lightning simulation data of three types of thundercloud above to determine the radial-temporal correlation and space correlation function. Besides, two correlation functions was used to identify the lightning activity parameters. As a result, values of lightning activity parameters and assumed initial value is not much difference. The difference in speed of cloud form I (dVI = 0.566 km/h), cloud form II (dVII = 2.724 km/h), and cloud form III (dVIII = 0.328 km/h). The difference in radius of cloud (dRI = 0.197 km, dRII = 1.762 km, dRIII = 0.251 km).The difference in storm duration (dTI = 4.42 minutes, dTII = 1.36 minutes, dTIII = 2.48 minutes). The number of cellthundercloud and the distance between the cell of thundercloud identified with the same initial value assumption.